Significance of Ground Motion Scaling Parameters on Amplitude of Scale Factors and Seismic Response of Short- and Long-Period Structures - Cavdar, Esengul; Ozdemir, Gokhan; Bayhan, Beyhan (Earthquake Engineering Research Inst, 2019)
In this study, an ensemble of ground motions is selected and scaled in order to perform code-compliant bidirectional Nonlinear Response History Analysis for the design purpose of both short- and long-period structures. The followed scaling method provides both the requirements of the Turkish Earthquake Code regarding the scaling of ground motions and compatibility of response spectra of selected ground motion pairs with the target spectrum. The effects of four parameters, involved in the followed scaling method, on both the amplitude of scale factors and seismic response of structures are investigated. These parameters are the number of ground motion records, period range, number of periods used in the related period range, and distribution of weight factors at the selected periods. In the analyses, ground motion excitations were applied to both fixed-base and seismically isolated structure models representative of short- and long-period structures, respectively. Results revealed that both the amplitudes of scale factors and seismic response of short-period structures are more prone to variation of investigated parameters compared to those of long-period structures.
Keywords: [No Keywords]